Paratuberculosis control strategies in dairy cattle: A systematic review (2022)
ABSTRACT: Background: Mycobacterium avium subsp. paratuberculosis is the causative agent of paratuberculosis (PTB), incurable enterocolitis, affecting domestic and wild ruminants. Economic losses, impacts on animal health and welfare, and public health concerns justify its herd-level control. Aim: To systematically collect information to answer: What are the control and eradication strategies of PTB in dairy cattle worldwide? Methods: The search procedure was carried out on October 2nd, 2019, and updated on August 3rd, 2021, using OVID®, SciELO, and Redalyc databases, and the registers from the International Colloquium on Paratuberculosis (1991–2018). The inclusion criteria considered articles published in English, Portuguese, and Spanish and in peer reviewed journals. The exclusion criteria included irrelevant topics, species other-than bovines, and not original articles. Definitive studies were obtained through the consensus of the authors on eligibility and quality. Data extraction was performed, considering bibliographic information, control and outcome strategies, follow-up time, and results. Results: Twenty-six relevant studies were found, reporting the use of three grouped control strategies: hygiene and management strategy (HMS), test-and-cull strategy (TCS), and vaccination strategy (VS). The HMS was the most common one (20/26), followed by TCS (17/26) and VS (7/26). Combined control strategies such as TCS-HMS (12/26), TCS-VS (1/26), and HMS-VS (1/26) were also described, and the consideration of the three control strategies (TCS-HMS-VS) was reported in two articles. The HMS included practices such as neonates/juvenile livestock hygiene, biosecurity, prevention of infection introduction into the herd, and environmental management. Within HMS, the most frequent practices were to remove calves from their dams as soon as possible after birth and to keep the minimal exposure of calves and heifers to adult cattle. As limitations, within the HMS, it is considered that some strategies cannot be included due to lack of compliance, or the application of the same strategy among one study and another may have a different degree of interpretation; publication bias was not controlled since the results of the control programs in endemic countries may be not available. Conclusion: The main PTB control strategies in dairy cattle worldwide are HMS, TCS, and VS. The use of one or several combined strategies has been found to succeed in controlling the disease at the herd-level.